1981
DOI: 10.1002/qj.49710745209
|View full text |Cite
|
Sign up to set email alerts
|

A field study of radiation fog in meppen, West Germany

Abstract: A field study of the microphysical properties of a radiation fog was conducted in Meppen, West Germany, on 17 February 1978. It is described and interpreted in terms of the prevailing meteorological conditions. Pronounced periodic fluctuations in liquid water content (intervals ∼70s) were observed at times in the radiation fog. It is suggested that these were a result of convective motions in the form of Bénard cells. the drop size distributions were broad, containing drops of radii up to 25 μm. Calculations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Meyer et al (1986) discuss a field project located at Albany, New York. Fuzzi et al (1992) present an overview of the Po Valley fog experiment in Italy, Choularton et al (1981) present a fog case in Germany, and Duynkerke (1991) presents observations of fog made in the Netherlands. To a greater or lesser degree all of these projects presented observations of stability within fog layers, and a discussion of the physics involved.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer et al (1986) discuss a field project located at Albany, New York. Fuzzi et al (1992) present an overview of the Po Valley fog experiment in Italy, Choularton et al (1981) present a fog case in Germany, and Duynkerke (1991) presents observations of fog made in the Netherlands. To a greater or lesser degree all of these projects presented observations of stability within fog layers, and a discussion of the physics involved.…”
Section: Introductionmentioning
confidence: 99%
“…A microphysical definition for fog has been studied (Tampieri and Tomasi, 1976;Pinnick et al, 1978;Chourlaton et al, 1981;Steward and Essenwanger, 1982;Minnis et al, 1992;Roach, 1994;Wetzel et al, 1996;Miles et al, 2000;Brenguier et al, 2000;Bendix, 2002). Then, Cermak and Bendix (2008) defined that the cloud optical thickness (COT) ranges from 0.5 to 30, and the effective radius (Re) varies between 3 and 12 µm with a maximum of 20 µm in coastal fog.…”
Section: Methodsmentioning
confidence: 97%
“…SPENCER et al (1976) found that the major effect on the droplet growth process was due to increased competition for vapor due to the nucleation of new droplets. However, CHOULARTON et al (1981) argued that large supersaturation fluctuations or convective motions near the fog top produced large drops in radiation fog. GERBER (1991) had a similar opinion about supersaturation.…”
Section: Burst Reinforcement and Droplet Spectrum Broadeningmentioning
confidence: 99%
“…Supersaturated environment (BARONTI and ELZWEIG, 1973), radiative cooling (ROACH, 1976a, b), and turbulent mixing (GERBER, 1981) were suggested to be the principal agents of droplet growth. However, the study of CHOULARTON et al (1981) indicated that larger drops cannot be produced by radiative cooling but by large supersaturation fluctuations or by convective motions. SPENCER et al (1976) suggested that the major effect upon the droplet growth process is from the increasing competition for vapor due to the nucleation of new droplets.…”
Section: Introductionmentioning
confidence: 99%